2014
DOI: 10.1186/s12968-014-0076-y
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution 3-dimensional late gadolinium enhancement scar imaging in surgically corrected Tetralogy of Fallot: clinical feasibility of volumetric quantification and visualization

Abstract: BackgroundThe extent of surgical scarring in Tetralogy of Fallot (TOF) may be a marker of adverse outcomes and provide substrate for ventricular arrhythmia. In this study we evaluate the feasibility of high resolution three dimensional (3D) late gadolinium enhancement (LGE) cardiovascular magnetic resonance (CMR) for volumetric scar quantification in patients with surgically corrected TOF.MethodsFifteen consecutive patients underwent 3D LGE imaging with 3 Tesla CMR using a whole-heart, respiratory-navigated te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Previous investigations evaluating the reproducibility of methods assessed the feasibility of 3D scar imaging in selected patient groups with acute, subacute and chronic myocardial infarction as well as left atrial, right atrial, and right ventricular scar . These studies have shown that 3D LGE imaging is technically feasible, with a good diagnostic value.…”
mentioning
confidence: 99%
“…Previous investigations evaluating the reproducibility of methods assessed the feasibility of 3D scar imaging in selected patient groups with acute, subacute and chronic myocardial infarction as well as left atrial, right atrial, and right ventricular scar . These studies have shown that 3D LGE imaging is technically feasible, with a good diagnostic value.…”
mentioning
confidence: 99%
“…The reduction in RVLS was considered to be related to the RV dilatation and gradual formation of RV myocardial fibrosis in rTOF . The multi‐view reduction in RVLS was correspondent with the extension phenomenon of late gadolinium enhancement (LGE) CMR that RV fibrosis was not only seen at surgical sites ‐ the RVOT, but also in sites remote from RVOT which were vulnerable to ischemic insult …”
Section: Discussionmentioning
confidence: 99%
“…LGE enhancement is associated with adverse clinical features in repaired tetralogy of Fallot (ToF) and RV scar is the substrate for ventricular arrhythmia. This study demonstrated high resolution 3D LGE at three Tesla findings in 15 patients using a whole heart, respiratory navigated technique and evaluated a semi-automated segmentation analysis [ 16 ]. Total right ventricular outflow tract scar volume using the semi-automated method was compared to manual segmentation as the gold standard in 15 patients with ToF.…”
Section: Congenital Heart Disease Pulmonary Arterial Hypertension Pmentioning
confidence: 99%